Self-Assembled Dual-Targeted Epirubicin-Hybrid Polydopamine Nanoparticles for Combined Chemo-Photothermal Therapy of Triple-Negative Breast Cancer - Li X (Dove Medical Press, 2020)
Xiang Li,1,* Qian Zou,1,* Jing Zhang,2 Peng Zhang,2 Xiong Zhou,1 Satya Siva Kishan Yalamarty,3 Xinli Liang,2 Yali Liu,4 Qin Zheng,2 Jianqing Gao5 1State Key Laboratory of Innovative Drug and Efficient Energy-Saving Pharmaceutical Equipment, Jiangxi University of Traditional Chinese Medicine, Nanchang 330006, Jiangxi, People’s Republic of China; 2Key Laboratory of Modern Preparation of TCM, Ministry of Education, Jiangxi University of Traditional Chinese Medicine, Nanchang 330004, Jiangxi, People’s Republic of China; 3Center for Pharmaceutical Biotechnology and Nanomedicine, Northeastern University, Boston, MA 02115, USA; 4College of Science and Technology, Jiangxi University of Traditional Chinese Medicine, Nanchang 330004, Jiangxi, People’s Republic of China; 5Institute of Pharmaceutics, College of Pharmaceutical Sciences, Zhejiang University, Hangzhou 310058, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jing ZhangKey Laboratory of Modern Preparation of TCM, Ministry of Education, Jiangxi University of Traditional Chinese Medicine, Nanchang 330004, Jiangxi, People’s Republic of ChinaTel/Fax +86 791 87118658Email 20101036@jxutcm.edu.cnPurpose: Folic acid and cyclic arginylglycylaspartic acid peptides were introduced to the surface of negatively charged lipid-coated hybrid polydopamine-cysteine cores for the delivery of epirubicin (EPI) (E/PCF-NPs). The combined chemo-photothermal therapy using E/PCF-NPs for triple-negative breast cancer was evaluated.Materials and Methods: The temperature elevation and thermal toxicity of nanoparticles were studied. The morphology and properties of E/PCF-NPs were characterized by transmission electron microscopy, scanning electron microscopy, and atomic force microscopy. Physicochemical properties, including particle size, zeta potential, drug loading, entrapment efficiency (EE%), stability and in vitro release, were determined. The cell viability, reactive oxygen species (ROS) levels, ratios of oxidized nicotinamide adenine dinucleotide to its reduced form (NAD+/NADH), apoptosis assays, and cellular uptake of E/PCF-NPs were determined on 4T1 cells. Pharmacokinetic studies and tissue distributions were performed and detected by an ultra-high performance liquid chromatography/mass spectrometry system. The antitumor effects of E/PCF-NPs under near-infrared (NIR) laser irradiation were also evaluated.Results: The sphere-like morphology of E/PCF-NPs showed a high EE%, uniform size of 106.7 nm, remarkable stability, and highly improved cytotoxicity under NIR laser, when compared to that of photothermal treatment alone. In vitro release of EPI from E/PCF-NPs was pH sensitive, and a greater response was achieved under NIR laser irradiation. Compared to chemotherapy or photothermal treatment alone, the combined treatment in vitro significantly inhibited the survival rate of 4T1 cells to 17.7%, induced ROS generation, and reduced NAD+/NADH significantly. Treatment with E/PCF-NPs under irradiation induced 4T1 cell apoptosis in approximately 93.6% cells. In vitro cellular uptake of E/PCF-NPs was time-dependent. The long-circulating and higher tumor accumulation of E/PCF-NPs resulted in complete ablation of breast tumor tissue through the enhanced photothermal effect by NIR laser irradiation-mediated cell apoptosis.Conclusion: E/PCF-NPs show enhanced anti-cancer effects due to synergistic effects of chemotherapy with photothermal therapy and may be potential therapeutic agents for cancer treatment.Keywords: polydopamine nanoparticles, L-cysteine, epirubicin, pharmacokinetics, triple-negative breast cancer